Risk and Protective Factors of Postpartum Depression using the Edinburgh Postnatal Depression Scale (EPDS) - Kadek Ayu Suarmini; Putu Dian Prima Kusuma Dewi; Putu Sukma Mega Putri; Ni Made Karlina Sumiari Tangkas; Alful Laila Okta Dewi (Indonesian Journal of Global Health Research, 2026)
Mental health remains a major global concern, as many physical and emotional health problems stem from unrecognized psychological disturbances. Postpartum depression (PPD) is among the most common mental health conditions affecting women after childbirth, with a global prevalence of depression and anxiety estimated at 15.6% during pregnancy and 19.8% during the postpartum period. This study aimed to identify the risk and protective factors associated with postpartum depression using the Edinburgh Postnatal Depression Scale (EPDS). A cross-sectional study was conducted among 58 postpartum mothers in the Gerokgak II Health Centre working area, Buleleng, Bali. Data were collected using a validated EPDS questionnaire consisting of 10 items assessing depressive symptoms over the past two weeks. The sampling technique used was total sampling, considering the limited number of postpartum mothers in the study area. Data were analyzed using logistic regression to determine significant predictors of postpartum depression.  The findings revealed that 7 mothers (12.7%) experienced postpartum depression. Maternal age was identified as a significant risk factor (p = 0.02, OR = 1.52), indicating that older mothers were more likely to develop postpartum depression. Conversely, the number of children (parity) acted as a protective factor (p = 0.04, OR = 0.032), suggesting that mothers with more children were less likely to experience depressive symptoms. Other variables such as age at marriage, reproductive age category, domicile, and employment status were not significantly associated (p > 0.05). Postpartum depression should not be regarded as a minor issue, as it can significantly affect maternal and infant well-being. Strengthening family and community support is essential to ensure early detection and effective prevention of postpartum depression.